Discovering neural signatures of alpha brainwave indicative of attentional effect during melodic and rhythmic quranic recitation: a study of Universiti Sains Malaysia Health Campus community - Shab, Mas Syazwanee (2024)
Attention is an established cognitive feature of alpha brainwaves (8-13 Hz). The Holy Quran has long been established to contribute to many psychological benefits, among others, the attentional effect. While research on the neuroscientific correlates of Quranic recitation is increasing over the past two decades, findings that project it to attention-inducing effect is scarce. In the present study, thirty (N=30) healthy participants (n Muslim=15, non-Muslim=15) were recruited and subjected to passive listening of five auditory stimuli, for three minutes each, consisting of Quranic and non-Quranic stimuli. To visualize the neural sources and the spectra of alpha power, the neuroimaging technique of complementary electroencephalography-magnetoencephalography (EEG-MEG) recording is used. The raw brain signals were processed and analysed using Brainstorm software. During the presentation of auditory stimuli, brain regions such as the precuneus, cuneus, calcarine, parietal and occipital showed significantly less neural activation, which reciprocated to higher alpha power. The increment in alpha power reflected attentional effect. The data underlines the idea that attention effect induced by Quranic recitation can plausibly be used to enhance attention level.